Managing the Auditor-Client Relationship Through Partner Rotations: The Experiences of Audit Firm Partners - Dodgson, Mary Kate; Agoglia, Christopher P.; Bennett, G. Bradley; Cohen, Jeffrey R. (The Accounting Review, 2020)
ABSTRACT While current audit standards explicitly state engagement partner tenure requirements, firms have flexibility in managing the rotation process. We conduct semi-structured interviews with 20 U.S. audit firm partners who share their experiences on topics including how they identify appropriate candidate partners and what efforts they undertake to manage relationships with clients post-rotation. We investigate firms' motivation to manage the auditor-client relationship through the lens of Social Exchange Theory (SET), and we consider how likely outcomes of this rotation process map onto regulators' intent that a newly rotated partner provides a fresh perspective to the audit. Our study informs regulators and investors about the process by which engagement partners are selected for rotation, documenting that partner assignment is typically not random. Further, our finding that partner rotation is an extended process (rather than a single discrete event) has implications for audit researchers investigating the effects of partner rotation.